Active maintenance of meiosis-specific chromosome structures in Caenorhabditis elegans by the deubiquitinase DUO-1 - Liesl G. Strand; Charlotte P. Choi; Savannah McCoy; Emmanuel T. Nsamba; Nicola Silva; Anne M. Villeneuve (Proceedings of the National Academy of Sciences, 2026)
Meiotic prophase is characterized by a dynamic program in which germ cells undergo a complex series of associations and dissociations of protein complexes that drive assembly, remodeling, and disassembly of meiosis-specific chromosome structures and dramatic changes in chromosome compaction. Failure to properly coordinate these processes can result in improper chromosome segregation, producing aneuploid gametes and inviable zygotes. Here, we investigate the roles of Caenorhabditis elegans DUO-1, an ortholog of mammalian ubiquitin-specific proteases USP26 and USP29, in mediating these dynamic chromosomal events during meiotic prophase. Cytological analyses of duo-1 null mutants indicate that loss of DUO-1 function leads to impaired assembly of meiotic chromosome axes and synaptonemal complexes (SCs), loss of integrity of meiotic chromosome axes, ineffective homolog pairing, premature separation of sister chromatids, and late-prophase chromosome decompaction. Further, axis/SC instability in duo-1 mutants correlates with depletion of REC-8 cohesin complexes and is accompanied by massive accumulation of early DSB repair intermediates. By using a dual-AID-tagged allele to deplete DUO-1 during meiotic development, we demonstrate that DUO-1 is continually required throughout meiotic prophase progression, to promote proper axis/SC assembly in early prophase, to maintain axis/SC stability during the late pachytene stage, and to promote/maintain chromosome compaction at the end of meiotic prophase. Together, our data emphasize the importance of mechanisms that actively maintain meiotic chromosome structure and meiosis-specific chromosome architecture throughout meiotic prophase and implicate DUO-1 as a key player in these active maintenance processes.